Comparison of the efficacy and safety of picosecond Nd:YAG laser (1,064 nm), picosecond alexandrite laser (755 nm) and 2% hydroquinone cream in the treatment of melasma: A randomized, controlled, assessor-blinded trial - Liang, Surong; Shang, Shuai; Zhang, Wensi; Tan, Ansheng; Zhou, Boyang; Mei, Xueling; Li, Linfeng (Frontiers in Medicine, 2023)
Background: Increasing numbers of studies demonstrated that picosecond lasers (Picos) were effective and safe for melasma. However, A limited number of randomized controlled trials (RCTs) regarding Picos contribute to a modest level of evidence. Topical hydroquinone (HQ) remains to be the first-line therapy. Objective: To compare the efficacy and safety of non-fractional picosecond Nd:YAG laser (PSNYL), non-fractional picosecond alexandrite laser (PSAL), and 2% HQ cream in the treatment of melasma. Method: Sixty melasma patients with Fitzpatrick skin types (FST) Ⅲ-Ⅳ were randomly assigned to the PSNY, PSAL, and HQ groups at a 1:1:1 ratio. Patients in PSNYL and PSAL groups received 3 laser sessions at 4-week intervals. The 2% HQ cream was applied twice daily for 12 weeks in patients of the HQ group. The primary outcome, the melasma area and severity index (MASI) score, was evaluated at weeks 0, 4, 8, 12, 16, 20, and 24. The patient assessment score by quartile rating scale was rated at weeks 12, 16, 20, and 24. Results: Fifty-nine (98.3%) subjects were included in the analysis. Each group showed significant change from baseline in MASI scores from week 4 to week 24. The MASI score in the PSNYL group showed the greatest reduction compared to the PSAL group (P=0.016) and HQ group (P=0.018). The PSAL group demonstrated comparable MASI improvement as the HQ group (P=0.998). The PSNYL group had the highest patient assessment score, followed by the PSAL group and then the HQ group, although only the differences between PSNYL and HQ groups at weeks 12 and 16 were significant. Four patients (6.8%) experienced recurrence. Other unanticipated events were transient and subsided after one week to six months. Conclusion: The efficacy of non-fractional PSNYL was superior to that of non-fractional PSAL, which was not inferior to 2% HQ, thus non-fractional Picos providing an alternative for melasma patients with FSTs III-IV. The safety profiles of PSNYL, PSAL, and 2% HQ cream were similar.